Lateral Dorsal Cutaneous Nerve and Anastomotic Branch to the Intermediate Dorsal Cutaneous Nerve: A Review of Cadaveric Data and Comparison with 3 Tesla MRI. Issue 1 (January 2022) - Shah, Vrajesh J.; Mitchell, Brendon; Ghetti, Claudio B.; Huang, Brady K.; Kent, William; Foran, Ian M.
Category: Other; Hindfoot Introduction/Purpose: The lateral dorsal cutaneous nerve (LDCN) and anastomotic branch to the intermediate dorsal cutaneous nerve (AICN) can be injured during foot and ankle surgery. Cadaveric specimen studies are limited by small sample size.1-11 We sought to use high-field 3-tesla (3T) magnetic resonance imaging (MRI) to examine a significantly larger cohort and obtain a more representative sample of the course of the LDCN and AICN. A more generalizable understanding of the course and position of these structures will aid surgeons intraoperatively in avoiding iatrogenic injury when performing the sinus tarsi approach, as well as during percutaneous intramedullary fixation of the 5th metatarsal. Methods: High-field 3T MRI studies performed between January 2015 to January 2020 were reviewed. Three blinded reviewers at a single academic center measured the coronal distances of LDCN and AICN from the fifth metatarsal styloid (5MS). Intraclass correlation coefficients (ICC) were calculated to assess reviewer reliability. Foot and ankle MRIs with major structural abnormalities, such as tumor or the presence of hardware, were excluded. Results: A total of 125 foot and ankle 3T MRIs were identified. Intraclass correlation coefficient was excellent at 0.87 for LDCN to 5MS and 0.88 for AICN to 5MS. The mean distance of the LDCN to the 5MS was 0.8 cm (range 0.3-1.4 cm, CI 0.8-0.8 cm) and that from the AICN to the 5MS was 2.1 cm (range 1.6-3.2 cm, CI 2.0-2.2 cm. Height had no significant correlation with the nerves' distance from bony landmarks with r values of 0.14 and 0.29 for the LDCN and AICN, respectively. Similarly, we did not find BMI to significantly correlate, with r values of 0.10 and 0.30 for the LDCN and AICN, respectively. Conclusion: Our study demonstrated the LDCN and AICN can be found on average 0.8 cm and 2.1 cm, respectively, above the 5MS with no clear association to patient height or BMI. Literature studying the range of distances the LDCN is found from the 5MS is scarce, but one study noted the range to be 0.7-1.2 cm, which is significantly smaller than our range of 0.3-1.4 cm.3 To our knowledge, our study is first to note the range of distances the AICN can be found from the 5MS, which is 1.6-3.2 cm.